Artificial intelligence technologies and compassion in healthcare: A systematic scoping review - Morrow, Elizabeth; Zidaru, Teodor; Ross, Fiona; Mason, Cindy; Patel, Kunal D.; Ream, Melissa; Stockley, Rich (Frontiers in Psychology, 2023)
Background: It is unclear how artificial intelligence (AI) technologies will affect compassion in healthcare systems worldwide. Objectives: To provide a comprehensive and balanced perspective of the nature of any association between AI technologies and compassion in healthcare. Method: Systematic scoping review following Joanna Briggs Institute method and eligibility criteria defined by constructs for ‘AI technologies’, ‘compassion’ and ‘healthcare’. Sources of evidence were Web of Science and PubMed (English language 2011-2022). Thematic analysis. Results: 3,124 articles screened, 197 included. Themes were: 1) Developments and debates: Concerns about AI ethics, healthcare jobs, and loss of empathy; Human-centered design of AI technologies for healthcare; Optimistic speculation AI technologies will address care gaps; Interrogation of what it means to be human and to care; Recognition of future potential for patient monitoring, virtual proximity, and access to healthcare; Calls for curricula development and healthcare professional education; Implementation of AI applications to enhance health and wellbeing of the healthcare workforce. 2) How AI technologies enhance compassion: Empathetic awareness; Empathetic response and relational behaviour; Communication skills; Health coaching; Therapeutic interventions; Moral development learning; Clinical knowledge and clinical assessment; Healthcare quality assessment; Therapeutic bond and therapeutic alliance; Providing health information and advice. 3) Gaps in knowledge: Educational effectiveness of AI-assisted learning; Patient diversity issues; Implementation of AI technologies; Safety and clinical effectiveness. 4) Key areas for development: Enriching education, learning and clinical practice; Extending healing spaces; Enhancing healing relationships. Conclusion: Compassion is reconceptualized as a human-AI system of intelligent caring. Implications for future research and practice are identified.